The proportionality of crime and punishment on children gradual criminal liability - Natteri, Shahrdad Darabi, Mohammad Dashtbani Roozbehani, Hosien Hashemi, Mohammad Ebrahim Shams (Opción, 2019)
In this article, criminal responsibility for Gradual Children in the Islamic Penal Code of 2013 emphasizing the principle of proportionality of crime and punishment is being investigated. For this purpose, first, the terms of criminal liability, the gradual or non-existent liability, the principle of the proportionality of the offense is unfishable by definition, our legal system approach, after the adoption of the new penal code, is the age of 18, and is the end of the childhood period. As a conclusion, the Islamic Penal Code of 2013 is in a privileged position in relation to the previous laws.